Gh_FBL43 regulates the resistance of Gossypium hirsutum to Verticillium wilt through jasmonic acid and flavonoid-related pathways - Zhao, Jieyin; Su, Xuening; Gao, Wenju; Wang, Tingwei; Wang, Yuxiang; Chen, Quanjia; Qu, Yanying (Frontiers in Plant Science, 2025)
F-box-LRR (FBL) genes play crucial roles in the response of plants to pathogen stress. This study involved a systematic analysis of the evolution of the FBL gene family in Gossypium hirsutum from a whole-genome perspective, and through expression pattern analysis combined with virus-induced gene silencing (VIGS), Gh_FBL43 was identified as a gene associated with resistance to Verticillium wilt in G. hirsutum. Further RNA-seq analysis revealed key pathways and genes regulated by Gh_FBL43. The G. hirsutum genome contains 57 FBL genes, which can be divided into five subgroups that were relatively conserved during the evolution of cotton. Expression analysis revealed that the expression level of Gh_FBL43 significantly increased under Verticillium wilt stress, with notable differences observed among extreme varieties. VIGS-meditated silencing of Gh_FBL43 was performed, and the leaves of the silenced plants presented chlorosis and necrosis, with the disease severity index (DSI) and disease severity rate (DSR) being significantly greater than those of the empty vector control plants. RNA-seq data from Gh_FBL43-silenced and control plants at 0 h and 24 h post-infection revealed 10,928 differentially expressed genes (DEGs), including 2,051 shared DEGs. Enrichment analysis combined with expression pattern analysis indicated that the silencing of Gh_FBL43 reduced the expression of genes in jasmonic acid (JA) and flavonoid-related pathways. In conclusion, our findings demonstrate the important role of the Gh_FBL43 gene family in conferring resistance to Verticillium wilt in G. hirsutum, potentially regulating this resistance through JA and flavonoid-related pathways, thereby laying a foundation for further elucidation of the molecular mechanisms by which Gh_FBL43 confers resistance to Verticillium wilt.